19 Forming a regional network group. (17th November 2016) - Major, D; Clappison, E; Purva, M
Abstract : Education providers in North East Yorkshire and North East Lincolnshire and Goole have come together to form the Simulation Partnership Advancing Regional Knowledge – SPARK. This initiative was created to strengthen partnership working and promotion of simulation based education within the region. SPARK's inaugural meeting was held to discuss and develop plans for the group. Terms of reference were set and common goals were noted. The chair and administrator for the group were elected at this meeting. Over the coming months the group plan to create a regional strategy for simulation based education and share best practice. The partnership hopes to raise the profile of clinical education within the area, improving the care given to our patients, thus improving their safety. To promote SPARK the group were officially launched at the HILS 5 year anniversary conference -- Educating to Improve Patient Care in April 2016. Members of the team with technical capabilities were challenged with developing a website to create an online presence for the group. The website was launched and can be found at www.spark-neynl.org.uk The group agreed an advertising and marketing strategy as to how the good work of the group would be communicated with others and also with the intention of recruiting others. Individuals were made responsible for each task identified, such as creation of newsletters and how to distribute. Impact on practice SPARK is the first Regional Network Group for the area 23 members have now joined the group Website is now launched and live First newsletter has been published Meetings have been set for 2016 The regions courses are being standardised in terms of delivery and content starting with the chest Drain Course